PENGARUH KOMPETENSI PROFESIONAL GURU DAN MINAT BACA SISWA TERHADAP HASIL BELAJAR AL QURAN HADIS KELAS X MAN BINTUHAN KABUPATEN KAUR - Muflihah Fithriani (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2020)
Abstract: The purpose of this study is to see the direct influence positively the professional competence of teachers on learning outcomes Quran Hadith, students read the learning outcomes Quran Hadith, and the professional competence of teachers and students read together the learning outcomes Quran Hadith class X Madrasah Aliyah Bintuhan Kaur regency. This research use as many as 136 students kuantitatif.Populasinya MAN Bintuhan Kaur regency. Research samples of 38.2% of the population, or as many as 52 students are students of class X2 and X4. The analysis technique used is the correlation (simple, double) with the data collection methods and dokumentasi.Data keosioner analyzed by using path analysis. The results showed a positive direct influence between the professional competence of teachers (0.477) 2 = 0.2275 = 22.75%, students’ reading interest (0.504) 2 = 0.2540 = 25.40%, and the professional competence of teachers and students read together (0.0707) 2 = 0.005 = 0.5% against the Quran Hadith learning outcomes of students in class X MAN Bintuhan Kaur regency.